Gerakan Sigap Stunting (Gesit) Melalui Penyuluhan Sosial dan Pelatihan Pengolahan Bahan Makanan Lokal di Desa Cikondang Kabupaten Sumedang - Saepudin, Asep; Widiansyah, Wiwit; Samosir, dkk, Irniyati (LPPM Universitas Koperasi Indonesia, 2024)
Stunting is a condition where a child has less length or height compared to age. This condition is measured by body length or height that is more than minus two standard deviations from the median of WHO child growth standards. Stunting is caused by insufficient nutritional intake over a long period of time due to providing food that does not meet nutritional needs. Stunting can occur when the fetus is still in the womb and only appears when the child is two years old. The purpose of this article is to describe social education activities and training on local food processing in an effort to overcome stunting. The series of social education activities and local food management training as an educational intervention program is expected to be able to overcome the occurrence of stunting in the community. The social education and local food processing training activities carried out consisted of the stages of identifying needs, preparing program design, implementing the program and evaluating the program. The results of social education and local food processing training for parents have been successful in increasing the community's entrepreneurial abilities, which in turn has an impact on increasing the economic capacity and welfare of the community, thereby preventing malnutrition in children.